Basic Psychological Needs and Emotions of Finswimming Athletes During the Training Phase - Putri Meidiana; Komarudin; Mochamad Yamin Saputra; Geraldi Novian (Universitas Negeri Semarang, 2025)
Background Problems: Finswimming face high psychological stress due to demands, competition, risk of injury, and challenging aquatic environments. Basic psychological needs and the ability to manage emotions are crucial factors in supporting athletes' mental well-being. Research Objectives: This study aims to explore the relationship between the fulfillment of basic psychological needs and emotions of finswimming athletes. Methods: The method used is quantitative descriptive using Basic Needs Satisfaction in Sport Scale (BNSSS) and Sport Emotion Questionnaire (SEQ). Subjects involving 30 finswimming athletes at the Shark Aquatic Club. Results: The results of the study showed a significant positive relationship between the fulfillment of basic psychological needs and the emotions of finswimming athletes. Data analysis revealed that when athletes' basic psychological needs are well met, they tend to be better able to manage emotions effectively. This indicates that increasing the fulfillment of psychological needs is related to increasing the ability to control emotions. Conclusion: This study concludes that there is a significant positive relationship between the fulfillment of basic psychological needs and the ability to manage emotions of finswimming athletes. This means that fulfilling psychological needs supports better emotions during the training phase. This study suggests paying more attention to meeting athletes' basic psychological needs in training programs to optimize athletes' mental well-being and performance.